1995
DOI: 10.1002/pssa.2211490219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ge4+ substitution in lithium ferrites

Abstract: X‐ray diffraction, infrared, and Mössbauer spectroscopy techniques are used to investigate Li0.5 + 0.5x GexFe2.5 ‐ 1.5xO4; x ≦ 0.5. The polycrystalline samples show single‐phase spinel structure. The lattice constant for x ≧ 0.2 is found to be nearly constant, but smaller than for x = 0. A small component of Fe2+ has been detected in the IR spectra. The Mössbauer absorption patterns give magnetic sextets superimposed on a paramagnetic component that increases with increasing germanium content. The average hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The experimentally determined lattice parameter value in the present study for the sample x = 0 is 8.385 Å has a good coincidence with that of the literature value 8.37 Å [12]. The difference between a th and a exp as shown in Figure 2 can be attributed to the deviation from the formula of cation distribution (3), and this deviation is related to the presence of divalent iron ions Fe 2+ [25] and other crystal imperfections.…”
Section: Cation Distribution and Theoretical Lattice Parametersupporting
confidence: 89%
“…The experimentally determined lattice parameter value in the present study for the sample x = 0 is 8.385 Å has a good coincidence with that of the literature value 8.37 Å [12]. The difference between a th and a exp as shown in Figure 2 can be attributed to the deviation from the formula of cation distribution (3), and this deviation is related to the presence of divalent iron ions Fe 2+ [25] and other crystal imperfections.…”
Section: Cation Distribution and Theoretical Lattice Parametersupporting
confidence: 89%
“…Several studies [1 to 4] have reported additions of divalent, trivalent and tetravalent ions and various parameters have been measured depending on the desired application. Our previous works have studied X-ray analysis, IR absorption and Mo È ssbauer effect of Li±Ge ferrites [5,6]. Also, the structure and different magnetic properties of Li±Ti ferrites were studied [7 to 9].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative density of states curve resulting from such a model is illustrated in Fig. 5 which refers to Lio.sFe2.504 that is usually an n-type semiconductor [6, 71. It is observed experimentally that G(a) passes through a sharp minimum at TD, which implies an increase in the conductivity activation energy in the disordered phase, i.e., w = w, + E , (9) where W, is the polaron hopping energy according to Austin and Mott [ll]. The term E may be due to the presence of disorder which should impede the motion of carriers, thus allowing more time for polaron formation and should also create regions in which the electron is more strongly localized.…”
Section: Order-disorder Transition Ofmentioning
confidence: 97%
“…The aim of this work is to study the conduction mechanism of polycrystalline Lio ~F e 2 5 0 4 and the effect of Ge4+ ions on this mechanisms. This work is a part of several works on the same composition (X-ray analysis and IR absorption [8], Mossbauer effect [9], and ac conductivity [lo]).…”
Section: Introductionmentioning
confidence: 99%